2022
DOI: 10.3390/foods11172586
|View full text |Cite
|
Sign up to set email alerts
|

Novel Probiotic/Bacterial Cellulose Biocatalyst for the Development of Functional Dairy Beverage

Abstract: The development of innovative functional products with potential health benefits, under the concept of bio-economy, is flourishing. This study undertook an evaluation of non-dairy lactobacilli Lactiplantibacillus pentosus B329 and Lactiplantibacillus plantarum 820 as “ready to use” starter cultures. Lactic acid bacteria (LAB) cultures were evaluated for their fermentation efficiency, before and after freeze-drying, using cheese whey (CW) as a fermentation substrate and subsequent immobilization on bacteria cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Moreover, the number of surviving bacteria in the fermented milk after the first batch increased to approximately 11.06 log CFU/g in the recycled batches and remained at this level throughout the tested reusable batches ( Figure 8 b). In another study, Lappa et al prepared a bacteria cellulose (BC) film as a novel biocatalyst for producing functional sour milk ( Figure 8 c) [ 30 ]. In this work, Lactiplantibacillus pentosus B329 and Lactiplantibacillus plantarum 820 were selected as starter cultures.…”
Section: Cellulose-based Probiotic Films For Food Applicationsmentioning
confidence: 99%
“…Moreover, the number of surviving bacteria in the fermented milk after the first batch increased to approximately 11.06 log CFU/g in the recycled batches and remained at this level throughout the tested reusable batches ( Figure 8 b). In another study, Lappa et al prepared a bacteria cellulose (BC) film as a novel biocatalyst for producing functional sour milk ( Figure 8 c) [ 30 ]. In this work, Lactiplantibacillus pentosus B329 and Lactiplantibacillus plantarum 820 were selected as starter cultures.…”
Section: Cellulose-based Probiotic Films For Food Applicationsmentioning
confidence: 99%
“…The loss of viability of probiotics during processing, storage, and after digestion has been widely documented [ 3 ], and it has been established that any food claiming to have a probiotic effect should contain at least 10 6 to 10 7 CFU/mL of viable probiotic bacteria [ 4 ], as health benefits are directly related to the number of viable cells present at the time of consumption [ 5 ]. Considering the human health implications of this issue [ 6 ], as well as the economic ones, since the global probiotic market is projected to increase to around USD 110 billion by 2030, new studies should be conducted to search suitable technologies to guarantee its cell viability [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that the probiotic bacterium Lactobacillus acidophilus 016 in bacterial cellulose nanofiber developed as a support material had a survival rate of 71% during 24 days of storage at 35 °C [ 9 ]. In another study, BC was used to preserve a probiotic L. plantarum strain prepared in a ready-to-use form for dairy products, retaining viable cells of 8 log CFU/g (from the initial cell number of 10 log CFU/g) after 5 months of storage at 4 °C [ 10 ]. It has also been shown to act as a physical barrier to reduce the deleterious effects of freezing and as a binding matrix for lactic acid bacteria [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%